AN ANALYSIS OF PERFORMANCE ASSESSMENT BASED ON KPKU - Mawirda Mawirda; Yulihasri Yulihasri (Universitas Muhammadiyah Jember, 2019)
Performance measurement is the main thing in conducting and the basis for evaluating and improving a company. Conducting continuous improvement and evaluation is an absolute requirement for companies with a vision to develop. Based on the results of research with the qualitative method carried out during the assessment of PT Mitra Kerinci's Superior Performance Assessment Criteria (KPKU), the following conclusions can be drawn: from the aspect of KPKU indicators that have been further analyzed by PT Mitra Kerinci through several processes such as 1. Application of the compilation Performance Appraisal based on PT Mitra Kerinci's Superior Performance Evaluation Criteria (KPKU) for the RNI Group's Superior Performance Assessment Criteria (KPKU) assessment which still uses partial. 2. The arrangement of Performance Appraisal based on PT Mitra Kerinci's Superior Performance (KPKU) evaluation criteria begins with completing and filling out a Questionnaire consisting of 13 items. 3. conducting an assessment of the seven criteria. 4. The third stage is to determine OFI (Opportunity for Improvement) as a result of the discussion of the Seven Superior Performance Assessment Criteria (KPKU). 5. Results of Performance Evaluation for superior and superior management practices.